Enzyme immunoassay for anti-treponemal IgG: screening or confirmatory test?. Issue 1 (January 1992) - Young, H; Moyes, A; McMillan, A; Patterson, J
Abstract : AIMS: To review the performance of the Venereal Diseases Research Laboratory (VDRL) test and the Treponema pallidum haemagglutination assay (TPHA) as a combined screen for syphilis to provide a baseline for assessing screening by anti-treponemal IGG EIA. METHODS: Between 1980 and 1987 all serum samples were screened by both VDRL and TPHA tests. The FTA-ABS test was also used in suspected early primary syphilis, or when one of the other tests was positive. A positive result in a screening test was confirmed by quantitative testing. From 1988 all specimens were screened with an enzyme immunoassay (Captia Syph G) as a single screening test. RESULTS: Of the 44 primary, 47 secondary, and 38 early latent cases of syphilis, the VDRL and TPHA detected 32 (73%) and 31 (71%) of the primary cases; the combination detected 37 (84%). All 85 cases of cases of secondary and early latent infection were reactive in the TPHA test, whereas the VDRL was reactive in only 68 (80%). EIA had a reported sensitivity of 82% for primary infection. CONCLUSIONS: EIA can be used as a single screening test for detecting early syphilis because its results are comparable with those of the combined VDRL and TPHA tests. The conventional VDRL test should not be used as a single screening test.